2015
DOI: 10.1016/j.jacc.2014.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Vascular Load in Calcific Degenerative Aortic Valve Stenosis

Abstract: Vascular function in calcific degenerative AS is conditioned by the upstream valvular obstruction that dampens forward and backward compression waves in the arterial tree. An increase in vascular load after TAVR limits the procedure's acute afterload relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 30 publications
4
74
0
5
Order By: Relevance
“…Collectively, the change from before TAVR to 30 days and 6 months after TAVR in each of these measures of arterial load was modest or absent although others have demonstrated acute increases in arterial load immediately after TAVR. 19 Arterial load parameters further stratified outcomes beyond SBP: patients with the worst outcomes had both a lower SBP and higher pulsatile arterial load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the change from before TAVR to 30 days and 6 months after TAVR in each of these measures of arterial load was modest or absent although others have demonstrated acute increases in arterial load immediately after TAVR. 19 Arterial load parameters further stratified outcomes beyond SBP: patients with the worst outcomes had both a lower SBP and higher pulsatile arterial load.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, focusing on valve hemodynamics alone may be inadequate as evidenced by a recent study showing increased vascular stiffness after transcatheter aortic valve replacement (TAVR). 19 Total vascular hydraulic load includes steady and pulsatile components. Steady load is represented by systemic vascular resistance, whereas pulsatile load is because of wave reflections and vascular stiffness.…”
mentioning
confidence: 99%
“…In AS patients referred for valve replacement, a higher arterial stiffness correlates with less LV mass regression and with more adverse cardiac events after SAVR [26] and TAVI [27]. Yotti et al [4] studied arterial function before and after TAVI and reported an increase in arterial load after the procedure resulting in a residual elevation of LV pressure in 70% of patients. Moreover, myocardial response to AS involves variable degrees of myocardial fibrosis [28], the extent of which correlates with NYHA functional class at baseline [29], and predicts the improvement in NYHA class after valve replacement [29].…”
Section: Assessment Of Tavi Outcome: Patients' Vs Physicians' Perspementioning
confidence: 99%
“…[13][14][15] The deleterious effects of increased arterial stiffness and pulsatile load in this population are vastly underappreciated although likely not remediable with medical therapy in advanced age.…”
Section: See Article By Lindman Et Almentioning
confidence: 99%